2007
DOI: 10.1029/2007gl030577
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of sonic layer depth from surface parameters

Abstract: [1] Sonic layer depth (SLD), an important parameter in underwater acoustics, is the near surface depth of first maxima of the sound speed in the ocean. The lack of direct observations of vertical profiles of velocimeters or temperature and salinity, from which sound speed and SLD can be calculated, hampers the investigation of SLD. In this study, we demonstrate SLD estimation using artificial neural network (ANN) from surface measurements that can be replaced with satellite observations later. Surface and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…NN is a massive parallel-distributed computer model consisting of simple processing units called artificial neurons that are the basic functioning units (more details are available in . It is proved that NN based estimations of mixed layer depth (Swain et al, 2006) and sonic layer depth (Jain et al, 2012) are better than those from the multiple regression method. ANN analysis requires three sets of data for (1) training, (2) verification and (3) validation.…”
Section: Methodsmentioning
confidence: 98%
“…NN is a massive parallel-distributed computer model consisting of simple processing units called artificial neurons that are the basic functioning units (more details are available in . It is proved that NN based estimations of mixed layer depth (Swain et al, 2006) and sonic layer depth (Jain et al, 2012) are better than those from the multiple regression method. ANN analysis requires three sets of data for (1) training, (2) verification and (3) validation.…”
Section: Methodsmentioning
confidence: 98%
“…It is shown that ANN-based estimations of mixed layer depth [20] and sonic layer depth [21] are better than those estimated from the multiple regression method. The ANN analysis requires three sets of data for (1) training, (2) verification, and (3) validation.…”
Section: Amf Developmentmentioning
confidence: 98%
“…In addition to various methods of estimations, artificial neural network (ANN) is another possible method to derive OHC from satellite observations over larger temporal and spatial scales. The ANN technique has proved its capability in the estimation of various oceanic parameters and subsurface information such as tropical cyclone heat potential (TCHP), mixed and sonic layer depths from the surface observations [19]- [22]. Ali et al [23] estimated the TCHP (the OHC from surface to the depth of 26 • C) from SST and SSHA through ANN approach.…”
Section: Introductionmentioning
confidence: 99%